Modeling of ecosystem services informs spatial planning in lands adjacent to the Sarvelat and Javaherdasht protected area in northern Iran. (February 2017) - Zarandian, Ardavan; Baral, Himlal; Stork, Nigel E.; Ling, Matthew A.; Yavari, Ahmad R.; Jafari, Hamid R.; Amirnejad, Hamid
Graphical abstract: Highlights: InVEST was used to map and estimate the effect of land use change on ecosystem services in the Hyrcanian forests in Iran. Forest loss results in loss of biodiversity, carbon sequestration and water balance. Scenario development explored the impacts of land use changes on ecosystem services. Collaborative Zoning scenario presents the best configuration of the landscape. This may lead to reduced environmental impact and less stakeholder conflict. Abstract: Dynamic models of ecosystem services supply and scenario analysis of changes in multiple services are being increasingly used to support land use planning and decision making. This approach reduces potential and real conflicts among various stakeholders potentially creating win–win solutions for all. It is particularly applicable in areas where insufficient land for agriculture and settlements is resulting in high rates of conversion of natural forest and grasslands. We quantified and mapped multiple ecosystem services, including habitat provision as a proxy for biodiversity, carbon storage and sequestration, and water balance and supply in the Sarvelat and Javaherdasht region of the globally-significant Hyrcanian (Caspian) forests in northern Iran using the Integrated Valuation of Ecosystem Services and Tradeoffs tool. This region is experiencing a rapidly increasing rate of forest conversion and as a result, the protected area located within the study landscape is threatened by human encroachment. Plausible future landscapes were modeled under three scenarios: (i) business as usual; (ii) protection-based zoning which reflects an expansion of the protected area boundary to prevent land use changes; and (iii) collaborative zoning through redefining the protection boundary simultaneously with an adjustment to meet local stakeholders' objective of expansion of anthropogenic cover. The results showed that the collaborative zoning scenario would best contribute to effective policy because it presents a more rational spatial configuration of the landscape maintaining the provision of ecosystem services. This scenario may lead to reduced environmental impacts while achieving less conflict between the government and local communities. These results will help to inform and shape natural resource management policies in Iran and is applicable elsewhere in the world.